TI_GERICHTE 11.2013.43 vom 19. Januar 2015 , Servitù di passo necessario, litisconsorzio necessario dei convenuti - TI Tribunale d'appello (2015)
Servitù di passo necessario, litisconsorzio necessario dei convenuti